Transition from decelerating to accelerating universe with quadratic equation of state in f(R, T) gravity. Issue 1 (2nd January 2019) - Ahmed, Nasr; Fekry, M.; Shaker, A. A.
ABSTRACT: In this paper, we have constructed a flat Friedmann-Robertson-Walker (FRW) cosmological model in f ( R, T ) gravity. The solution of Friedmann equations has been obtained assuming the quadratic equation of state p = α ρ + β ρ 2, where α and β are parameters. The model describes an accelerating universe with positive energy density, negative pressure and negative cosmological constant. The behaviour of the deceleration parameter shows that the universe accelerates after an epoch of deceleration in a good agreement with recent observations. The non-conventional scenario for an accelerating universe with negative cosmological constant has been discussed.